A New Model for Constructing Poverty Lines - Nanak Kakwani (Philippine Institute for Development Studies (PIDS), 2010)
In this paper, we present a new model for constructing poverty lines. The model uses consumer theory to construct both food and nonfood poverty thresholds. Although one cannot completely eliminate the value judgments inherent in the construction of poverty thresholds, this model helps to make the ad hoc assumptions that are generally made more justifiable. The model ensures that poverty line is consistent across regions. The methodology developed in the paper is used to illustrate the construction of poverty thresholds in Pakistan.
Keywords: 330; economies of scale; poverty measures; poverty line; consistent poverty line; consumer theory; calorie cost; Armut; Grundbedürfnisse; Messung; Skalenertrag; Konsumtheorie; Pakistan